An Anticipated Study On Burnout Among Secondary School Teachers - Dr.G.Muruganantham, Dr.P.Ponraj, Dr. Dr.M.Mahendraprabu, Dr.S.Shobana (International Journal of Advanced Science and Technology, 2020)
In today's fast paced world of competitive work places with enriched curriculum and crowded class room, enhanced emotional level help the teachers to decrease the stress, increase productivity understand emotion as they happen and interact positively with those around. Hence emotional maturity and academic achievement, it becomes necessary to assess the level of emotion of future teachers' gains its importance. Due to management involvement, parents interference, technological advancements, media influence style of living etc., class room management of teachers has become a difficult task and teachers with high burnout. It is not need of the hour, keeping in view of the above mentioned facts the present paper attempts to assess the level of burnout among secondary grade teachers.